Anti-proliperative and Anti-metastatic Agents of Balinese Long Pepper (Piper retrofractum V) Extract in Breast Cancer - Made Violin Weda Yani; Varennia Bhargah; I Gede Agus Darsana Palgunadi; Ni Putu Sri Indrani Remitha; I Made Winarsa Ruma (Journal of Health Science and Prevention, 2020)
Breast cancer is malignancy that becomes significant health problem in the world. According to WHO data in 2018, there were 2.1 million cases of breast cancer with mortality rate reaching 627,000. Current breast cancer treatments are surgery, radiation therapy, hormonal therapy and chemotherapy. However, these treatments have side effects such as neuropathy, fatigue after undergoing chemotherapy, and alopecia. Natural ingredients are the choice to overcome these weaknesses, one of which is the utilization of piperine in Balinese long pepper (Piper retrofractum Vahl). Piperine can increase the bioavailability of many drugs by increasing absorption from the intestine, suppressing the metabolism of drugs in lung and liver tissue by inhibiting CYP3A4 and P84 glycoprotein P84. Piperine is easily absorbed in the intestine and excreted through urine and feces, causing minimal toxic effects. Piperine in Balinese long pepper is able to reduce breast cancer cell proliferation by 40%. Piperine can also inhibit epidermal growth factor (EGF) by inducing decreased expression of MMP-9 and MMP-13. Piperine will work through inhibition of NF-ÎºB and PKCÎ± phosphorylation and AP-1 activation by interfering extracellular signal-regulated kinase (ERK) signaling pathway (ERK) 1/2, p38 MAPK, and Akt which results in inhibition of migration and metastasis of breast cancer cells.